Improvement On The Nutritional Quality Of Larval Feeds For Gilthead Seabream: Rotifer Feeds And Early Weaning Diets - Eryalçin, Kamil Mert (2019)
Programa de doctorado: Acuicultura Sostenible y Ecosistemas Marinos Aquaculture is rapidly growing in the Mediterranean region. Particularly, gilthead sea bream (Sparus aurata) and sea bass (Dicentrarchus labrax) are the two most important marine fish species commercially produced, together with two new species the meagre (Argyrosomus regius) and the Senegalese sole (Solea senegalensis). However, a weak point in marine fish production is still larviculture and the increase in health and survival to produce high quality juveniles. Marine fish larvae are poorly developed at first feeding and their performance is directly affected by the nutritional quality of live feeds and weaning diets. Fatty acids, amino acids, vitamins and minerals should be well balanced and in sufficient amounts in the diets in order to fulfill the whole needs of newly hatched larvae. Marine food web chains start from microalgae, main producers of essential nutrients for marine fish larvae. The nutritional values of wild live preys such as copepods are superior to hatchery live feeds. Under this point of view, the aim of the present thesis was to optimize the nutritional quality of live preys and early weaning diets for marine fish. For that purpose, the effect of different commercial rotifer diets versus microalgae on production performance and nutritional composition of rotifers have been studied. The results showed that, Nannochloropsis oculata biomass was highly nutritious and very efficient for rotifer production in the form of spray-dried (Chapter 1). In dry diets for marine fish larvae, fish oil and fishmeal are highly nutritious but limited ingredients. Therefore, other ingredients must be investigated and used for sustainable growth of larviculture. Instead of fish oil, microalgae oil or single cell oils are highly recommended due to a more simple composition of fatty acids and the lack of pollutants. Essential fatty acids originated from different microalgae can effectively replace fish oil. These microorganisms can produce DHA ...